PRAWO W UTOPII KOMUNISTYCZNEJ. ZARYS PROBLEMATYKI - Kuźmicz, Karol (Zeszyty Prawnicze, 2016)
LAW IN THE COMMUNIST UTOPIA. AN OUTLINE OF TOPIC Summary The Communist Utopia is strictly connected with the philosophical concepts of Karl Marx and Friedrich Engels in the 19th century. It is based on historical and dialectical materialism, which were later developed by younger philosophers who created Communist ideology. The scientific character of Communism was stressed and they claimed that it is possible to reach Communism, which will be the highest achievement of social development of progressive mankind. According to XI thesis about Ludwig Feuerbach “the philosophers have interpreted the world in many ways, but the clue problem is to change the world”. In order to change the world law was supposed to be used, because the philosophers claimed that it is easier to create a new man and new world than to adapt the system to people. The transition to Communism, with its first phase called „real socialism”, was connected with the fight of classes, which was supposed to be sharper and sharper. In this fight the law had to be both sword and shield on the way to Communism. The law was used as a tool in this fight against „relics of capitalism” such as: counter-revolution, imperialism, non-socialist attitude towards ownership and labor, nationalistic prejudices, religion and many other relics of capitalism. The Communist ideology presumed that reaching the power would be achieved by the revolution. In political and legal practice the ideology was totalitarian. The Communist system has elaborated its own theory of state and law, according to which the law was regarded as a tool for rulers, who wanted to achieve their own goals (often Utopian). The revolutionary movement tried to preserve the changes by binding law. As a result of it the law was instrumentally treated by the regime, which itself was above the law. The Communism, which as a presumption was not Utopian, has occurred to be anti-Utopian (so called negative Utopia). According to Leszek Kołakowski, the Communism was a “total lie” from the beginning. The highest point of the Communist Utopia was a presumption that at the end of the revolution the state and law will not be necessary any more. The non-class society will reach Communist paradise on the earth.